1990
DOI: 10.1113/expphysiol.1990.sp003445
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of action of magnesium on acetylcholine‐evoked secretory responses in isolated rat pancreas

Abstract: SUMMARYThis study investigates the effects of magnesium (Mg2+) on acetylcholine (ACh)-evoked secretory responses and calcium (Ca2+) mobilization in the isolated rat pancreas. ACh induced marked dose-dependent increases in total protein output and amylase release from superfused pancreatic segments in zero, normal (1 1 mM) and elevated (10 mM) extracellular Mg24.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

1993
1993
2000
2000

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(19 citation statements)
references
References 22 publications
1
18
0
Order By: Relevance
“…In (Lennard & Singh, 1992), we demonstrated that basal [Mg2+]I changes during perturbation of extracelluar Mg2+. Taken together, these results corroborate previous findings using acetylcholine (Francis et al 1990) that an alteration in cellular Mg2+ can influence secretagogue-evoked exocrine secretion in the pancreas. Vicinal diones are reagents which are recognized to react with and modify arginine residues in proteins (Lundblad & Noyes, 1984).…”
supporting
confidence: 82%
“…In (Lennard & Singh, 1992), we demonstrated that basal [Mg2+]I changes during perturbation of extracelluar Mg2+. Taken together, these results corroborate previous findings using acetylcholine (Francis et al 1990) that an alteration in cellular Mg2+ can influence secretagogue-evoked exocrine secretion in the pancreas. Vicinal diones are reagents which are recognized to react with and modify arginine residues in proteins (Lundblad & Noyes, 1984).…”
supporting
confidence: 82%
“…The pancreas of either normal or diabetic female rats was dissociated into acinar cells with collagenase in two stages totalling 75 min by established methods (Francis et al 1990b;Francis & Singh, 1990). Pancreatic acinar cells were loaded with 2 ìÒ fura_2-acetomethylester (AM) by methods described previously (Francis et al 1990a).…”
Section: Measurement Of [Ca¥]é In Pancreatic Acini and Acinar Cellsmentioning
confidence: 99%
“…Concerning the precise mechanism for this action of catecholamines on Mg 2+ movements, an increase in the affinity of the Mg 2+ transporter for intracellular Mg 2+ through cAMPactivated phosphorylation has been postulated (86). (43,44,102,152,153). In these experiments, the individual enzyme and total protein secretion were determined by on-line automated methods (152,(154)(155)(156)) based on either fluorimetric or colorimetric measurements.…”
Section: Other Tissuesmentioning
confidence: 99%
“…(43,44,102,152,153). In these experiments, the individual enzyme and total protein secretion were determined by on-line automated methods (152,(154)(155)(156)) based on either fluorimetric or colorimetric measurements. The same effect of high [Mg 2+ ] o is observed in isolated intact pancreas with respect to the pancreatic flow rate and total protein output (44).…”
Section: Other Tissuesmentioning
confidence: 99%
See 1 more Smart Citation